2007
DOI: 10.1093/aje/kwm085
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to Mild Cognitive Impairments, Dementia, and Death: Findings from the Nun Study

Abstract: The potential of early interventions for dementia has increased interest in cognitive impairments less severe than dementia. However, predictors of the trajectory from intact cognition to dementia have not yet been clearly identified. The purpose of this study was to determine whether known risk factors for dementia increased the risk of mild cognitive impairments or progression from mild cognitive impairments to dementia. A polytomous logistic regression model was used, with parameters governing transitions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 40 publications
(54 reference statements)
7
117
2
1
Order By: Relevance
“…For example, in the Nun Study, 14.5% of subjects with MCI returned to normal cognition after 11 years of follow-up. 3 Subjects more often stayed in their current cognitive state than transitioned to another, which was observed among the ADC subjects as well. Both studies may have underestimated the proportion of subjects returning to normal cognition, as clinicians are not blinded to previous patient diagnoses; clinicians may be disinclined to assign a diagnosis of normal cognition for a patient previously diagnosed as MCI.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, in the Nun Study, 14.5% of subjects with MCI returned to normal cognition after 11 years of follow-up. 3 Subjects more often stayed in their current cognitive state than transitioned to another, which was observed among the ADC subjects as well. Both studies may have underestimated the proportion of subjects returning to normal cognition, as clinicians are not blinded to previous patient diagnoses; clinicians may be disinclined to assign a diagnosis of normal cognition for a patient previously diagnosed as MCI.…”
Section: Discussionmentioning
confidence: 57%
“…1 However, several longitudinal epidemiologic studies have found that transition from an MCI diagnosis back to normal cognition is fairly common. [2][3][4][5][6][7][8][9] Estimates of transition from MCI back to normal cognition have been quite varied, ranging from 4% to 15% [2][3][4][5] in clinic-based studies and 29% to 55% 6 -9 in population-based studies, depending in part on duration of follow-up. To date, few, if any, studies have focused on the subset of subjects who return to normal cognition after an MCI diagnosis.…”
mentioning
confidence: 99%
“…In effect, 74% of this association remained unexplained. Memory deficits are critical to the diagnosis of mild cognitive impairment (Brayne, 2007;Gauthier et al, 2006) which is itself linked to progression to dementia (Tschanz et al, 2006;Tyas et al, 2007). More than a half people with mild cognitive impairment progress to dementia within 5 years (Gauthier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The tools used to diagnose intact cognitive status, MCI, and dementia have been described in previous Nun Study publications. 15 Briefly, participants classified as cognitively intact had scores within normal limits on 4 cognitive tests in the neuropsychological battery of CERAD. 16,17 They also had intact global cognitive ability as measured by the MiniMental State Examination (MMSE) 18 and were intact regarding activities of daily living (ADL).…”
Section: Methodsmentioning
confidence: 99%